An efficient heterologous Escherichia coli-based expression system for lectin production from Pleurocybella porrigens. Issue 3 (31st December 2020) - Suzuki, Tomohiro; Nakamura, Luna; Inayoshi, Satomi; Tezuka, Yuki; Ono, Akiko; Choi, Jae-Hoon; Dohra, Hideo; Sasanami, Tomohiro; Hirai, Hirofumi; Kawagishi, Hirokazu
ABSTRACT: In this study, we report a more efficient heterologous expression of lectin from Pleurocybella porrigens (PPL) using an Escherichia coli -based expression system. The yield (9.3 mg/L culture broth) of recombinant PPL (rPPL) using this expression system was increased approximately 9-fold compared to our previous study. The rPPL obtained in this study exhibited the same biochemical properties as the native PPL.